THE INFLUENCE OF LIVE STREAMING ON IMPULSIVE BUYING BEHAVIOR TOWARD READY-TO-WEAR CLOTHING PRODUCTS: (A SURVEY ON TIKTOK-USING STUDENTS IN BANDUNG AREA) - Shelvira Azka Afifah; Koernia Purwihartuti; Nazofatullidya Nazofatullidya (Politeknik Negeri Ambon, 2025)
Introduction: The advancement of digital technology has transformed consumer behavior patterns, particularly in online shopping activities through live-streaming features. This feature offers a real-time interactive experience that has the potential to trigger impulsive buying behavior, especially among university students as active social media users. This research explores how specific live-streaming elements on TikTok impact the impulsive purchase behavior of ready-to-wear clothing products among university students in Bandung. The constructs and indicators used were developed by integrating findings from previous studies. Method: A quantitative approach was employed through a survey of 423 respondents, and the data were processed using PLS-SEM, incorporating an analysis of second-order constructs. A key contribution of this study lies in the integration of diverse indicators from earlier research, combined with a focused investigation of an underexplored demographic and regional context. Results: The findings indicate that live-streaming exerts a statistically significant and positive influence on impulsive buying behavior, and that all dimensions forming live-streaming contribute to increasing the intensity of impulsive purchases, proving this marketing strategy is effective. These findings offer theoretical contributions to the study of digital consumer behavior and practical implications for fashion business actors, particularly those in the ready-to-wear segment. Keywords: online shopping, digital marketing, e-commerce, digital interaction, social media